1984
DOI: 10.1080/00268948408078687
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Physical Properties of a Two-Dimensional Organic Metal, Di[bis(ethylenedithiolo)tetrathiofulvalene] triiodide, (BEDT-TTF)+2I3

Abstract: Electrical oxidation of bis(ethylenedithiolo)tetrathiofulvalene (BEDT-TTF) 1 in a nitrogen saturated tetrahydrofurane solution containing (n-C4HIO)4N+I:i' as electrolyte results in the deposition of crystal plates of (BEpT-TTF)rI3' (CIOHgSshI3' These two dimensional crystals are triclinic, space group PI, a = 9.211(2), b = 1O.S50 ( 4) behave like a two dimensional metal. while below 135 K a metal-insolator transition occurs. The thermopower values indicate that the high temperature conductivity is dominated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
226
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 399 publications
(237 citation statements)
references
References 15 publications
(8 reference statements)
11
226
0
Order By: Relevance
“…The nearly isotropic conductivity in the (ab)-plane is typically between 60 and 250 (f2cm)-l at room temperature; Ub/Ua ::::: 2 and Ub/Uc ::::: 4000 [2]. The compound undergoes a metal insulator transition at TMI = 135 K. A large number of studies have dealt with the nature of this phase transition [1][2][3][4][5][6][7][8][9], but very little progress has been made. The sudden opening of an energy gap was originally attributed to the formation of a charge density wave (CDW) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nearly isotropic conductivity in the (ab)-plane is typically between 60 and 250 (f2cm)-l at room temperature; Ub/Ua ::::: 2 and Ub/Uc ::::: 4000 [2]. The compound undergoes a metal insulator transition at TMI = 135 K. A large number of studies have dealt with the nature of this phase transition [1][2][3][4][5][6][7][8][9], but very little progress has been made. The sudden opening of an energy gap was originally attributed to the formation of a charge density wave (CDW) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The a phase of di-[bis(ethylenedithiolo)tetrathiofulvalene]tri-iodine was the first organic material which showed highly conducting properties in two dimensions [1]. The nearly isotropic conductivity in the (ab)-plane is typically between 60 and 250 (f2cm)-l at room temperature; Ub/Ua ::::: 2 and Ub/Uc ::::: 4000 [2].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ␣Ј-͑BEDT-TTF͒ 2 IBr 2 showed semiconductive behavior above and below 200 K with only activation energy showing a change at this temperature. 1,2 Although Raman spectroscopy suggested that CO was already present above 200 K, 24 NMR showed a clear CO transition at 200 K. The difference between two measurements is due to their respective time scale. Raman spectroscopy can resolve fast phenomenon, whereas NMR can resolve slower phenomenon, less than ϳ MHz.…”
Section: E Relation Between Co Transition and Spin Gap Generationmentioning
confidence: 96%
“…Among these salts, the ␣ and modifications, each of which has a double column structure tilted toward each other, [1][2][3][4] have quarter-filled band structures, whereas the modification, which has strong dimeric structure, 5,6 has an approximately half-filled band structure. 7 It is important for quarter-filled systems to examine both the on-site Coulomb repulsion, U, and the off-site Coulomb repulsion, V, and these systems are likely to show charge-order ͑CO͒ state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation